EFFECTIVENESS OF POSTURAL THERAPY IN INFANTS WITH FREQUENT INTESTINAL COLIC - Т. Сорокман; В. Остапчук (Bukovynian State Medical University, 2023)
Infantile colic is a general term used to describe excessive crying, abdominal pain, and discomfort in the first months of life, and it causes stress for parents and concern for clinicians. Colic in babies is common all over the world. The Rome criteria offer diagnostic criteria for functional gastrointestinal symptoms but do not discuss their treatment. Manipulative treatments are considered effective interventions to reduce the severity of symptoms. The aim of the study. To evaluate the effectiveness of postural therapy in infants with intestinal colic. Methods. The current prospective cohort study used data from a mother-child cohort. 37 "mother-child" pairs (age of babies from 2 weeks to 4 months) were under observation. Two observation groups were created by the method of simple randomization: Group I - 17 infants who received traditional therapy (preparations based on simethicone, prokinetics, enzymes, antispasmodics, in case of significant flatulence, a gas removal tube or microenema was used), Group II - 20 infants who received postural therapy. To reveal the statistical difference between indicators in groups distributed normally, the Student's t-criterion of reliability was used, the degree of significance - r. The probability of the difference between relative values was determined by the Fisher's angular transformation method (Рφ). The research design and all the methods used in this study were reviewed and approved by the bioethics commission of the Bukovinian State Medical University (protocol No. 8, dated 02/17/2023). The study was carried out as part of the research work «Early diagnosis, treatment and prevention of combined pathology of the gastrointestinal tract and thyroid gland in children» (state registration number 0116U002937, implementation period 02.2016-11.2022). Results of the study. In 81.1% of babies, colic started after the 2nd week of life, in 18.9% - after the 1st month of life. The average age of onset of symptoms was 1.1 ± 0.1 months. Initially, colic occurred less often (1-2 times a week) and lasted up to 15 minutes, with age, their frequency and duration increased. We identified the main risk factors for the development of colic in babies: younger age of parents (F = 0.529, p = 0.001), mother's smoking (F = 0.498, p = 0.01), hypodynamia of the mother during pregnancy (F = 0.511, p = 0 .02), positive history of the father regarding functional diseases of the gastrointestinal tract (F = 0.788, p= 0.004), positive history of the mother regarding functional diseases of the gastrointestinal tract (F = 0.489, p= 0.01), food allergy in the mother (Ф = 0.476, p = 0.02), food allergy in the father (F = 0.329, p = 0.05), early (up to 3 months) transfer of the child to mixed or artificial feeding (F = 0.324, p = 0.05), hypoxic-ischemic CNS damage (F = 0.467, p = 0.05), body weight at birth <2900 g (F = 0.531, p = 0.01). The dynamics of symptoms in children of both observation groups was almost the same, with the exception of such signs of colic as flatulence and grunting, which disappeared faster by 2.7±0.6 days in children who were on postural therapy. The frequency of colic attacks also decreased. Positive dynamics of body weight gain were noted in infants of both groups. Conclusions. 1. The average age of onset of intestinal colic symptoms in infants was 1.1 ± 0.1 months. 2. The relationship between the age of the parents, the mother's smoking and the mother's hypodynamia during pregnancy, a positive history of the parents regarding functional diseases of the gastrointestinal tract, hypoxic-ischemic lesions of the central nervous system and a birth weight of less than 2900 g and intestinal colic in infants was established. 3. The use of postural therapy in infants with intestinal colic is an effective method of their treatment, which is confirmed by the positive dynamics of symptoms, a decrease in the frequency and duration of colic attacks, a sufficient increase in body weight and does not require the cost of medication.